2012
DOI: 10.1186/2049-1891-3-43
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary ratio of n-6 to n-3 polyunsaturated fatty acids on immunoglobulins, cytokines, fatty acid composition, and performance of lactating sows and suckling piglets

Abstract: This experiment was conducted to investigate the effects of dietary ratios of n-6:n-3 polyunsaturated fatty acids (PUFA) on the performance of lactating sows and their piglets. Thirty pregnant Landrace sows were assigned to one of three treatments from d 108 of gestation until weaning (26–29 d) and were fed diets containing different ratios of n-6:n-3 PUFA including 3:1, 9:1 and 13:1. The effects on sow and litter production traits were examined together with an assessment of sow body condition. No differences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
52
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(63 citation statements)
references
References 30 publications
6
52
0
2
Order By: Relevance
“…Dietary low n-6:n-3 fatty acid ratio in mice on a high fat diet, did not differ significantly in BW among the groups at any point throughout the study (Riediger et al 2008). According to Yao et al (2012) no differences were detected among the treatments for the daily feed intake of sows or changes in sow weight and back-fat levels during lactation. According to Yao et al (2012) no differences were detected among the treatments for the daily feed intake of sows or changes in sow weight and back-fat levels during lactation.…”
Section: Results and Discussion Reproductive Performance Of Sowsmentioning
confidence: 76%
See 2 more Smart Citations
“…Dietary low n-6:n-3 fatty acid ratio in mice on a high fat diet, did not differ significantly in BW among the groups at any point throughout the study (Riediger et al 2008). According to Yao et al (2012) no differences were detected among the treatments for the daily feed intake of sows or changes in sow weight and back-fat levels during lactation. According to Yao et al (2012) no differences were detected among the treatments for the daily feed intake of sows or changes in sow weight and back-fat levels during lactation.…”
Section: Results and Discussion Reproductive Performance Of Sowsmentioning
confidence: 76%
“…For instance, Rooke et al (2001) found that piglets from sows fed diets containing tuna oil (which is a source rich in n-3 PUFA) had a more active suckling behavior immediately after birth, which contributes to their enhanced growth during the entire lactation period. Indeed, Yao et al (2012) demonstrated that altering the ratio of n-6:n-3 PUFA in lactating sow diet had an effect on performance of suckling piglets, and it tended to increase the litter ADG when dietary ratio of n-6:n-3 PUFA was 9:1. Indeed, Yao et al (2012) demonstrated that altering the ratio of n-6:n-3 PUFA in lactating sow diet had an effect on performance of suckling piglets, and it tended to increase the litter ADG when dietary ratio of n-6:n-3 PUFA was 9:1.…”
Section: Growth Performance Of Pigletsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eastwood et al (2014) observed increased EPA in sow milk following ALA supplementation. Yao et al (2012) demonstrated that altering the PUFA ratio from n-6:n-3 to 9:1 in the diet of lactating sows influenced immunoglobulin and cytokine levels and tended to increase litter performance and piglet immune status.…”
Section: Discussionmentioning
confidence: 99%
“…Esses teores apresentam-se satisfatórios quando comparados a outras fontes de nutrientes já conhecidas, conforme Tabela 4. MARQUES, 2008;LI et al, 2010;MALPELI et al, 2012;ESCUDERO et al, 2012;VILCHE et al, 2013;COSTA, BORGES, 2005;BORGES et al, 2010; O principal interesse nessa semente refere-se ao teor de ácidos graxos poli-insaturados ácido alfa-linolênico (18:3 n-3, LNA), e ácido linoleico (18:2 n-6, LA) (AYERZA, 2009;MOHD et al, 2012), tendo em vista que esses compostos auxiliam as funções imunológicas, inibem a proliferação de linfócitos e citocinas pró-inflamatórias, atuam na prevenção de incidência de doenças cardiovasculares e mantém a integridade das membranas celulares e dos neurotransmissores (YAO et al, 2012;LUDWIG et al, 2013).…”
Section: Semente De Chiaunclassified